Hill land utilisation in Ulster - Symons, Leslie (Statistical and Social Inquiry Society of Ireland, 1956)
This paper examines the use of hill land in Ulster at the present time, with particular emphasis on the improvements being undertaken to reduce the gap between present and potential productivity and with consideration of some of the problems arising out of fuller utilisation.
Read before the Society, 9 December 1955
Keywords: Hill land utilisation; Northern Ireland agriculture; Regional development; Agricultural productivity; 314.15